Gaya Camat Dalam Penegakkan Disiplin Pegawai Pada Kantor Camat Pangean Kabupaten Kuantan Singingi - Witri Habibah; Abdul Sadad (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Leadership in an organization greatly influences employees, especially the style applied by a leader to influence employees to be ethical and behave in accordance with applicable norms. In accordance with the Kuantan regent's regulations, article 5 number 37 of 2018 concerning the obligation to be a leader to guide and direct subordinates to behave ethically in carrying out their duties. This is related to the style applied by the Pangean sub-district head in the Pangean sub-district head's office, Kuantan Singingi Regency. The purpose of this research is to find out the style of the Pangean sub-district head and what factors hinder the sub-district head in enforcing employee discipline in the Pangean sub-district office. The theory used in the research is the theory of Hersey and Blancard in Pasalong(2013:50-51) which uses indicators of leader instruction style, leader consultation style, leader participation style, and leader delegation style. A qualitative descriptive research method was used, which involved collecting data through observation and interviews as well as documentation. Data analysis used includes collection, reduction, presentation and drawing conclusions. According to the research results, the sub-district head's style in enforcing employee discipline in the Pangean sub-district sub-district office in terms of instructions is quite optimal, seen from the implementation of morning and afternoon roll calls, there the sub-district head can provide motivation and direction to employees. In terms of consultation, it doesn't play a role because the sub-district head doesn't consult enough with employees when employees commit violations. In terms of participation, it is good and in terms of delegation, the sub-district head is quite good, but it must be improved so that employees can be disciplined well, so that they can provide satisfaction to the community and the goals they achieve. planned can be achieved optimally